Big data and data ownership rights: The case of car insurance. Issue 1 (10th April 2023) - H Rubin, Tzameret; Aas, Tor Helge; Williams, Jackie
Customers' data points sources are growing, through the Internet of Things (IoT), telematics and interfacing with third parties' platforms. Third parties provide either by-product data about their clients, or data that are generated for the specific task of a more accurate measurement of behaviour. One of the core building blocks in insurance is understanding risk – therefore, innovation around data points (sources and analytics) to proxy risk is the engine behind its digital transformation. While the value of data points is clear for the providers of insurance products and services, the customers have not only less control over their data, but also hardly benefit from the creation of those data points. In this paper we provide a case study from the British car insurance industry, about a data-driven product that pivoted into a re-designed personal data right architecture, which included transparency, traceability and usability of customers' digital traces, and enabled customers' ownership rights over their data.